2009
DOI: 10.1007/s11240-009-9638-3
|View full text |Cite
|
Sign up to set email alerts
|

Prolific shoot regeneration of Astragalus cariensis Boiss

Abstract: Prolific shoot regeneration via organogenesis was induced from leaf and leaf petiole explants of the endemic Astragalus cariensis species on Murashige and Skoog (MS) medium with a-naphthaleneacetic acid (NAA) and benzyladenine (BA) within 8 week. The highest number of shoots (23/explants) was obtained from leaf explants cultured on MS with 0.5 mg/l NAA and 4 mg/l BA. Elongated shoots were successfully rooted in MS medium with 0.5 mg/l indole-3-butyric acid. Rooted plantlets were acclimatized in pots containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
(7 reference statements)
4
11
0
2
Order By: Relevance
“…But, it was observed that MS with 2.5 mg/l BAP alone was the most efficient treatment for multiple shoot induction on cotyledons than the combinations. On the contrary positive synergistic effect of cytokinins like BAP or Kn or TDZ or 2iP or zeatin in combination with an auxin like IAA, or NAA on in vitro shoot regeneration through organogenic differentiation has been reported by several workers (Shen et al 2007, Unda et al 2007, Erisen et al 2010, Ghimire et al 2010, Lin et al 2011, Wadl et al 2011, Mandal and Laxminarayana 2012, Perez-Jimenez et al 2012and Bhagya et al 2013. Superior effect of BAP for shoot multiplication has been reported among various medicinal plants of Asteraceae, like Tanacetum cinerariifolium (Hedayat et al 2009), Spilanthes acmella (Saritha and Naidu 2008), Launaea sarmentosa (Mahesh et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…But, it was observed that MS with 2.5 mg/l BAP alone was the most efficient treatment for multiple shoot induction on cotyledons than the combinations. On the contrary positive synergistic effect of cytokinins like BAP or Kn or TDZ or 2iP or zeatin in combination with an auxin like IAA, or NAA on in vitro shoot regeneration through organogenic differentiation has been reported by several workers (Shen et al 2007, Unda et al 2007, Erisen et al 2010, Ghimire et al 2010, Lin et al 2011, Wadl et al 2011, Mandal and Laxminarayana 2012, Perez-Jimenez et al 2012and Bhagya et al 2013. Superior effect of BAP for shoot multiplication has been reported among various medicinal plants of Asteraceae, like Tanacetum cinerariifolium (Hedayat et al 2009), Spilanthes acmella (Saritha and Naidu 2008), Launaea sarmentosa (Mahesh et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The failure of 2,4-D to induce shoot formation on petal explants of St. John's wort is consistent with published reports of its inhibitory effect on shoot regeneration from leaf and anther explants of this species (Pretto and Santarem 2000;Murch and Saxena 2002). Astragalus cariensis, callus generated on a medium with 2,4-D and kinetin, did not produce shoots (Erisen et al 2010). However, in the presence of high sucrose levels, 2,4-D in combination with BA induced embryogenic callus formation on carnation petals (Karami et al 2008).…”
Section: Shoot Regenerationmentioning
confidence: 92%
“…To our knowledge, although there are some previous reports on callus induction and shoot regeneration in some species of other Leguminosae family plants, to date no successful method has been reported for shoot regeneration from callus of S.alopecuroides L, [2,3,[9][10][11]13]. In these species, callus differentiation and shoot regeneration were determined by growth regulators [2][3][9][10]. In addition, other studies on Astragalus species also described various calli types that were formed during callus induction, associated with shoot regeneration.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, callus production is also a necessary step for obtaining protoplasts used in protoplast fusion, a useful tool in genetic improvement of vegetatively propagated Sophora's species for introducing useful genes or producing new crops [4]. To our knowledge, although there are some previous reports on callus induction and shoot regeneration in some species of other Leguminosae family plants, to date no successful method has been reported for shoot regeneration from callus of S.alopecuroides L, [2,3,[9][10][11]13]. In these species, callus differentiation and shoot regeneration were determined by growth regulators [2][3][9][10].…”
Section: Introductionmentioning
confidence: 99%